2016
DOI: 10.15288/jsad.2016.77.873
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis Involvement and Nonsuicidal Self-Injury: A Discordant Twin Approach

Abstract: ABSTRACT. Objective: Cannabis use, particularly at an early age, has been linked to suicidal thoughts and behavior, but minimal work has examined the association between cannabis use and lifetime nonsuicidal self-injury (NSSI). The current study aims to characterize the overlap between lifetime and early cannabis use and NSSI and to examine genetic and environmental mechanisms of this association. Method: Adult male and female twins from the Australian Twin Registry (N = 9,583) were used to examine the odds of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 44 publications
(45 reference statements)
2
15
0
Order By: Relevance
“…Significant genetic correlations between cannabis use, depression and self‐harm were also in line with some , but not all previous findings in family studies. The genetic correlation between cannabis use and depression estimated here was higher than those previously published using the same methodology , probably reflecting the increased power of more recent depression GWA analyses.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Significant genetic correlations between cannabis use, depression and self‐harm were also in line with some , but not all previous findings in family studies. The genetic correlation between cannabis use and depression estimated here was higher than those previously published using the same methodology , probably reflecting the increased power of more recent depression GWA analyses.…”
Section: Discussionsupporting
confidence: 88%
“…In addition to depression, cannabis use has also been associated with increased rates of self‐harm, both for non‐suicidal and suicidal behaviours. This phenotypic association may be stronger than that observed between cannabis and depression, but while some studies have reported evidence of a shared genetic aetiology , others found that genetic factors were less important . Therefore, additional work exploring how cannabis use related to self‐harm is also needed.…”
Section: Introductionmentioning
confidence: 97%
“…Despite evidence of significant interactions between cannabis phenotypes with sex and alcohol use, stratified analyses suggested that this pattern of association was consistent across sex, smoking or alcohol consumption. Significant genetic correlations between cannabis use, depression and self-harm were also in line with some [15,23,24], but not all [16] previous findings in family studies. The genetic correlation between cannabis use and depression estimated here was higher than those previously published using the same methodology [13], probably reflecting the increased power of more recent depression GWA analyses.…”
Section: Phenotypic and Genetic Relationships Between Cannabis Use Dsupporting
confidence: 77%
“…In addition to depression, cannabis use has also been associated with increased rates of self-harm, both for non-suicidal [19][20][21] and suicidal [16,22,23] behaviours. This phenotypic association may be stronger than that observed between cannabis and depression, but while some studies have reported evidence of a shared genetic aetiology [23,24], others found that genetic factors were less important [16,25]. Therefore, additional work exploring how cannabis use related to self-harm is also needed.…”
Section: Introductionmentioning
confidence: 97%
“…The disinhibition theory argues that cannabis intoxication leads to disinhibition, which, in turn, directly increases users’ risk for self‐injury (Delforterie et al., ). It is also possible that variables not considered in the present analyses (e.g., attention‐deficit/hyperactivity disorder, childhood sexual abuse) might increase risk for both conditions (Few et al., ). Finally, as noted by Few and colleagues (), repeated exposure to 9‐tetrahydrocannabinol (THC) and endocannabinoids through chronic cannabis use could also potentially modulate users’ pain perception, thereby increasing their risk for self‐injury, particularly nonsuicidal self‐injury.…”
Section: Discussionmentioning
confidence: 99%